A Study on the Norms of Toeplitz Matrices with the Generalized Mersenne Numbers - , Sevda Aktas, Yuksel Soykan (Archives of Current Research International, 2023)
In this article presents findings related to Toeplitz matrices with Mersenne numbers. We started by creating Toeplitz matrices whose components are Mersenne numbers. We then calculated the Euclidian, row and column norms of these matrices and established both lower and upper bounds for their spectral norms. Additionally, we determined the upper bounds for the Frobenius and spectral norms of the Kronecker and Hadamard product matrices of the Toeplitz matrices with Mersenne numbers.